The last ambassador a novel - Kalb, Bernard 1922-2023; Kalb, Marvin L. 1930- (Little, Brown and Company, 1981)
A fictional account of American Ambassador Hadden Walker's final days in South Viet Nam before Saigon's fall to the North Vietnamese